Long-term outcomes of nasopharyngeal carcinoma treated with helical tomotherapy using simultaneous integrated boost technique: A 10-year result - Meng, Lingling; Teng, Feng; Liu, Qiteng; Du, Lei; Cai, Boning; Xie, Chuanbin; Gong, Hanshun; Zhang, Xinxin; Ma, Lin (Frontiers in Oncology, 2023)
Background: To evaluate the long-term survival and treatment-related toxicities of nasopharyngeal carcinoma (NPC) patients treated with helical tomotherapy (HT). Methods: One hundred and ninety newly diagnosed non-metastatic NPC patients treated with HT from September 2007 to August 2012 were analyzed retrospectively. The dose at D95 prescribed was 70-74Gy, 60-62.7Gy and 52-56Gy delivered in 33 fractions to the primary gross tumor volume (pGTVnx) and positive lymph nodes (pGTVnd), the high risk planning target volume (PTV1), and the low risk planning target volume (PTV2), respectively, using simultaneous integrated boost technique. The statistical analyses were performed and late toxicities were evaluated and scored according to the Common Terminology Criteria for Adverse Events (version 3.0). Results: The median follow-up time was 145 months. The 10-year local relapse-free survival (LRFS), nodal relapse-free survival (NRFS), distant metastasis-free survival (DMFS) and overall survival (OS) were 94%, 95%, 86%, and 77.8%; respectively. Fifty (26.3%) patients had treatment-related failures at the last follow-up visit. Distant metastasis, occurred in 25 patients, was the major failure pattern. Multivariate analysis showed that age and T stage were independent predictors of DMFS and OS, Concomitant chemotherapy improved overall survival, but anti-EGFR monoclonal antibody therapy failed. The most common late toxicities were mainly graded as 1 or 2. Conclusions: Helical tomotherapy with simultaneous integrated boost technique offered excellent long-term outcomes for NPC patients, with mild late treatment-related toxicities. Age and clinical stage were independent predictors of DMFS and OS. And, concurrent chemotherapy means better OS. Further prospective study is needed to confirm the superiority of this technology and to evaluate the roles of anti-EGFR monoclonal antibody treatment.